Broomrapes in Major Mediterranean Crops: From Management Strategies to Novel Approaches for Next-Generation Control - Demosthenis Chachalis; Eleni Tani; Aliki Kapazoglou; Maria Gerakari; Angeliki Petraki; Francisco Pérez-Alfocea; Purificación A. Martínez-Melgarejo; Markus Albert; Khalil Khamassi; Mohamed Kharrat (BioTech)
Broomrapes (Orobanche and Phelipanche spp.) are parasitic weeds that significantly impact the productivity of major crops in the Mediterranean region, like tomato (Solanum spp.) and faba bean (Vicia faba) species. This review article extensively discusses management strategies to control broomrapes, which range from preventive measures to curative approaches. Additionally, it includes meaningful information on the intricate molecular mechanisms underlying the broomrape–host interaction, focusing on the host recognition of parasitic plant molecular patterns and the hormonal crosstalk that regulates the establishment of parasitism. Moreover, this article highlights the potential of breeding for resistance in cultivated crops, such as tomato and faba bean, as a sustainable, long-term solution to combat broomrape infestation. This review serves as a valuable resource for both researchers and farmers, offering insights for developing, implementing, and adapting effective and environmentally sustainable management practices for broomrape in Mediterranean agricultural systems.